Ekstrak Metanol Buah Sonneratia alba J.E.Sm sebagai Penghambat Pertumbuhan Helminthosporium sp. yang diisolasi dari Daun Jagung - Ari Hepi Yanti, Tuti Kusumadewi, Siti Khotimah (Universitas Tanjungpura, 2014)
Control of corn leaf blight caused by the fungus Helminthosporium sp., can be carried out by employing natural antifungal of plant extract. One of the plants that have the potential as an antifungal is Sonneratia alba J.E.Sm. The aim of this study is to determine the ability of S. alba fruit as antifungal and to determine the concentration of S. alba fruit extract, that can inhibit the growth of fungus Helminthosporium sp., at the level of very strong activities. Testing of antifungal activity of the fruit extract of S. alba carried out by employing 7 treatments, which the treatments are negative control, solvent control (DMSO 10%), positive control (Dithane M45 10%), concentration of fruit extracts S.alba (25 %, 50%, 75% and 100%). Based on phytochemical test indicates that fruit S. alba contains class of flavonoid compunds, alkaloids and tannins. The results of antifungal testing at level 100% concentration indicate very strong antifungal activity (90.01%). Those conditions indicate that 100% constitutes concentration of S. alba fruit extract, that can inhibit the growth of Helminthosporium sp. fungus at the level of very strong activities.